Autoeficácia em uma comunidade universitária de São Luís – MA: associação com o nível de atividade física - SILVA, Thaliane Maia (2022)
Introduction: The practice of physical activity is a type of predictive behavior in health that can be influenced by variables such as gender, income, education, and self-efficacy. Self efficacy refers to a set of personal beliefs that leads the individual to the awareness of their capabilities and potential that influence the change in lifestyle. Objective: to analyze the practice of physical activity with the perception of self-efficacy of servers (teachers and technical-administrative) and students of the Federal University of Maranhão - UFMA, São Luís campus. Materials and methods: this is a cross-sectional study of a descriptive nature. with a quantitative approach. A total of 1,783 subjects from UFMA, São Luís campus were included in the research. Sociodemographic data and data on self-efficacy and physical activity were collected using a specific questionnaire, the Map of Physical Activity and Health (MAFIS). Self-efficacy was measured through 10 questions describing the interviewees' ability to change attitudes towards lifestyle habits associated with health and quality of life. For the combined analysis of self-efficacy and its relationship with physical activity, the Hosmer Lemeshow test and the Qui-Square were used. Results: The findings indicated that self-efficacy is associated with three independent variables: gender, income and level of physical activity. Regarding gender, men are 73% more likely to have high self efficacy compared to women (OR: 1,73; IC: 1,28-2,34). Income was associated with self efficacy for physical activity, the data showed that individuals who do not have income (salary) are more likely to have low self-efficacy for exercise (p=0,23; IC95%: 1,07- 1,14; OR: 1,05), with a 5% increase in self-efficacy levels for physical activity. exercise of respondents as their monthly income grew. Self-efficacy was consistently linked to physical activity level; for this variable, the results showed that individuals who practice physical activity are more likely to have high self-efficacy compared to those who do not have this habit (IC95%: 1,99-3,56; OR:2,66). No associations were found between self-efficacy and age, education and skin color. Significant associations of self-efficacy with chronic non communicable diseases (NCDs), medication use and discomfort/pain were found. Conclusion: self-efficacy is associated with the level of physical activity, gender and monthly income of respondents. Higher levels of self-efficacy facilitate adherence and adherence to physical activity, however, monthly income, work routine, studies, household activities and chronic non-communicable diseases can negatively impact exercise self-efficacy, especially among women. women, thus raising the rates of sedentary behavior and physical inactivity among this group.